Compositing prevulcanized natural rubber with multiwalled carbon nanotubes to make antistatic films. (21st January 2022) - Wiroonpochit, Panithi; Keawmaungkom, Sutthinee; Chisti, Yusuf; Hansupalak, Nanthiya
Abstract: Natural rubber was prevulcanized using ultraviolet (UV) light and the resulting prevulcanized natural rubber (PVNR) was composited with multiwalled carbon nanotubes (MWCNT) as a conductive filler, to make films suitable for antistatic gloves. These films were characterized in terms of mechanical properties and electrical resistivity. Effects of type of UV radiation and other specifics of the production process, on mechanical properties of neat PVNR were first investigated. This was followed by an investigation of the effects of surfactant type on the dispersion of MWCNT in water and the PVNR matrix. Four surfactants with different headgroups were used in preparing MWCNT dispersions that were then mixed with the PVNR latex to form the different films. As a consequence of its milk‐like turbidity, the natural rubber latex was found to require deeply penetrating UVA light for satisfactory prevulcanization. Sodium dodecyl sulfate (SDS) was the best surfactant for dispersing MWCNT both in water and in PVNR matrix. SDS resulted in MWCNT–PVNR composite films with the least electrical resistivity and good mechanical properties for making antistatic gloves. SDS did not interfere with stress transfer at NR–MWCNT interface. SDS was superior to the other surfactants because its head group had a charge opposite to that on the NR surface and lacked a benzene ring that would have interacted strongly with the hydrophobic surface of MWCNT.